Use of propidium monoazide coupled with real-time PCR methodology to evaluate Escherichia coli O157 lethality in beef burgers after organic acid addition - Rey, María De Los Ángeles (2025)
In order to achieve bacterial inactivation in beef burgers, one of the alternatives proposed is to add organic acids as part of their formulation. The aim of this work was to evaluate the effectiveness of propidium monoazide coupled to qPCR (PMA-qPCR) as counting methodology to assess the addition of lactic acid (LA), caprylic acid, and fumaric acid (FA) alone and combined as inactivation agents on Escherichia coli O157 (both non-toxigenic and Shiga toxin-producing E. coli-[STEC]-strains). The effects on physicochemical properties were also evaluated. PMA-qPCR targeting stx2 and uidA genes allows quantifying STEC and non-toxigenic E. coli O157. The most effective acid combination was LA + FA for non-toxigenic E. coli O157 with a reduction of 1.06 log CFU/g measured by PMA-qPCR. However, this treatment increased hardness and chewiness once the beef burgers were cooked. Moreover, cooking weight loss was negatively affected by the addition of all organic acids tested. PMA-qPCR methodology permits to detect and quantify viable but nonculturable E. coli O157 in the beef burgers, a common limitation encountered in the traditional plate count method. The presence of bacteria in this metabolic state could explain differences among the values obtained by both methodologies. Addition of organic acids to beef burger formulations was not as effective as expected to inactivate E. coli.